UCHealth and General Electric: the importance of storytelling in marketing - Neisser, Drew (Henry Stewart Talks, 2019)
This case study explores the use of artful storytelling in advertising. Through an analysis of UCHealth and GE’s marketing campaigns, this case study concludes that storytelling is beneficial for both B2C and B2B businesses.